Efektivitas Stretching terhadap Kelelahan Kerja Operator Head Truck Terminal Petikemas Semarang - Salsabila, Khairunnisa Salmaa; Fajariani, Ratna; Widjanarti, Maria Paskanita (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2024)
Head truck operator is one of the jobs that is at risk of experiencing work fatigue at the Semarang Container Terminal. Based on the results of measuring work fatigue using the IFRC subjective self rating test questionnaire on 20 head truck operators, 25% experienced low fatigue, 55% moderate fatigue, and 20% high fatigue. One of the alternative fatigue management can be done by static stretching which is considered more efficient in adjusting to the company's work processes and more effective than other methods. This study aims to determine the effectiveness of stretching on work fatigue of Semarang Container Terminal head truck operators. This research was a quasi-experimental study with a pre-post test one group design. Respondents were head truck operators at the Semarang Container Terminal with a total of 49 respondents out of a total of 147 operators. This study used the Subjective Self Rating Test questionnaire from IFRC to measure work fatigue. The data analysis technique used was the paired t-test. The results of this study indicate that there is a significant difference in head truck operators after stretching with p-value of 0.000 with large effect (d = 7.44). In Conclusion There was an effectiveness of stretching on work fatigue of Semarang Container Terminal head truck operators.